Nursing Care for Post Op Orif Femur Fracture Patients with Ambulation Support Interventions in the Special Surgery Room Rsud Jenderal Ahmad Yani Metro Year 2024 - Puspitasari, Ika; Sugiarto, Sugiarto; Wardoyo, Eko (INDOGENIUS, 2025)
Background and Objectives: Femur fractures are one of the leading causes of complications and death that require proper management to prevent morbidity, complications, and accelerate patient recovery. The management of femur fractures includes pharmacological and non-pharmacological approaches, one of which is ambulation support. The purpose of this scientific work is to describe nursing care in postoperative patients with femur fractures through innovative ambulation support interventions. Methods: This research design uses a case study on a postoperative patient with a femur fracture, with early ambulation interventions carried out every day for 3 days of care. Results: The results showed increased left limb mobility, decreased edema, and tingling, and decreased pain intensity from scale 5 to scale 3 after 3 days of treatment. Conclusion:  Early ambulation as part of postoperative management of femur fracture is effective in reducing pain, improving mobility, and accelerating patient recovery. This approach can be adopted in nursing practice to improve the postoperative rehabilitation process.